PI3K functions as a hub in mechanotransduction. Issue 11 (November 2021) - Di-Luoffo, M.; Ben-Meriem, Z.; Lefebvre, P.; Delarue, M.; Guillermet-Guibert, J.
Abstract : Mammalian cells integrate different types of stimuli that govern their fate. These stimuli encompass biochemical as well as biomechanical cues (shear, tensile, and compressive stresses) that are usually studied separately. The phosphatidylinositol 3-kinase (PI3K) enzymes, producing signaling phosphoinositides at plasma and intracellular membranes, are key in intracellular signaling and vesicular trafficking pathways. Recent evidence in cancer research demonstrates that these enzymes are essential in mechanotransduction. Despite this, the importance of the integration of biomechanical cues and PI3K-driven biochemical signals is underestimated. In this opinion article, we make the hypothesis that modeling of biomechanical cues is critical to understand PI3K oncogenicity. We also identify known/missing knowledge in terms of isoform specificity and molecular pathways of activation, knowledge that is needed for clinical applications. Highlights: Class I and class II phosphatidylinositol 3-kinase (PI3K) activation is necessary for the rapid intracellular signal transduction of all mechanical stresses (shear, tension, compression); among those, kilopascal-range compressive stress promotes strong engagement of class I PI3Ks. Class I PI3Ks are upstream activators of the YAP/TAZ pathway; mechanical stress is permissive for their control of YAP/TAZ and targeting of PI3K is a novel strategy to hinder YAP/TAZ oncogenic dependence. In response to tension, integrins, cadherins, and ion channels undergo conformational changes, which initiates diverse cytosolic signals including hyperactivation of the class I PI3Ks. The cytoskeleton forms a rigid network that responds to physical forces. Early signal events lead to PI3K activation to activate small GTPases controlling actin cytoskeleton remodeling. Nutrient availability and metabolic state control the cell's adaptive response to mechanics via PI3Ks; mechanics induce PI3K-dependent rewiring of cell metabolism (class I) and autophagy (class II).